HUBUNGAN BEBERAPA FAKTOR DALAM PARTISIPASI PRIA PADA VASEKTOMI DI KECAMATAN GETASAN KABUPATEN SEMARANG JAWA TENGAH 2018 - Citra Erlinda Br. Munthe; Yudhy Dharmawan; Sri Winarni; R. Djoko Nugroho (Jurnal Kesehatan Masyarakat (Undip), 2019)
Data from BKKBN shows that women who are participants in family planning tend to be done by women (93.6%). Getasan sub-district is a sub-district in Semarang Regency which has the highest coverage of active male family planning participation of 618 men (7%). Purpose: The purpose of this study was to analyze the relationship of male knowledge about vasectomy, male attitudes toward vasectomy, cultural values about vasectomy, access to vasectomy services and men's perceptions regarding the side effects of vasectomy use with male participation in vasectomy. Method: This type of research is explanatory research using a case control design with a non-probably sampling method that is purposive sampling, the scale in this study is nominal scale using the contingency coefficient statistical test, the population in this study were all EFA men who used and did not use a vasectomy as many as 1922 couples, the sample in this study were 40 men (20 case samples and 20 control samples). Result: Univariate test results found that men had poor knowledge (55%), the same attitude (50%),%), supporting cultural values (70%), access to the same vasectomy services (50%) and good perceptions (95%). ) The bivariate test results from this study indicate that the male perception variable related to the side effects of vasectomy is a variable associated with male participation in vasectomy (x2 = 15.8, p value = 0.01, C = 0.53) with a strong relationship (value C approaches C maximum = 0.53). Male knowledge variable about vasectomy (x2 = 0.96, p value = 0.39, C = 0.15), male attitudes toward vasectomy (x2 = 0.41, pvalue = 0.52, C = 0.10), value cultural values of vasectomy (x2 = 1.66, pvalue = 0.19, C = 0.20), and access to services about vasectomy (x2 = 0.01, p value = 1.00, C = 0.01), is a variable that is not related to men's participation in vasectomy. Suggestions from this study are the need for counseling, advocacy, internal assistance and evaluation so that EFA men are ready to use a vasectomy.